2014
DOI: 10.1186/1479-5876-12-157
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of mesenchymal stem cells leads to reduced inflammation and cartilage damage in murine antigen-induced arthritis

Abstract: BackgroundRheumatoid arthritis (RA) is a debilitating and painful disease leading to increased morbidity and mortality and novel therapeutic approaches are needed. The purpose of this study was to elucidate if mesenchymal stem cells (MSCs) injected in the joints of mice with arthritis are therapeutic, reducing joint swelling and cartilage destruction.MethodsMurine mesenchymal stem cells (mMSCs) were isolated from bone marrow of C57Bl/6 mice and expanded in culture. Cells were tested for immunophenotype and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
95
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 27 publications
6
95
2
3
Order By: Relevance
“…Previous studies have shown that injected MSCs can migrate to injured lungs, livers, kidneys, and colons [1115182934]. In the present study, the use of CM-DiI facilitated tracking of injected MSCs [2338]. A large number of systemically administered CM-DiI-labeled cAT-MSCs were detected in the injured pancreas, which was confirmed by PCR amplification of cRPS5, the canine-specific reference gene [5].…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have shown that injected MSCs can migrate to injured lungs, livers, kidneys, and colons [1115182934]. In the present study, the use of CM-DiI facilitated tracking of injected MSCs [2338]. A large number of systemically administered CM-DiI-labeled cAT-MSCs were detected in the injured pancreas, which was confirmed by PCR amplification of cRPS5, the canine-specific reference gene [5].…”
Section: Discussionsupporting
confidence: 71%
“…3 To our knowledge this is the first clinical controlled trial with autologous BM-SC stimulated in vivo with a single intra-articular injection for the treatment of knee OA. Our study differs from other research developed in [24][25][26][27][28][29] In humans, other studies have been performed using stem cells from different collection sites such as adipose tissue [30][31][32][33] or peripheral blood through apheresis. 34,35 Some studies include case series and clinical trials with BM mesenchymal cells; some of them administered the cells by means of surgical intervention 13,[36][37][38] and others with intra-articular injection.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have shown that MSCs injected intra-articularly are retained at the injection site for 1–4 weeks, without migration to distant organs such as the lungs, spleen, and liver [30, 31]. …”
Section: Discussionmentioning
confidence: 99%